HUBUNGAN KEMAMPUAN LITERASI SAINS DENGAN PEMECAHAN MASALAH IPA SISWA SEKOLAH DASAR - Yohamintin Yohamintin; Yayah Huliatunisa (Indonesian Journal of Elementary Education (IJOEE), 2022)
AbstractThe purpose of this study was to determine the relationship between scientific literacy skills and science problemsolving for fourth grade students of Sukatani IV public elementary school, Tangerang Regency, using correlationalquantitative research methods, with 56 research subjects for fourth grade students. The test instrument used scientificliteracy skills essay questions (X). which consists of 10 questions, and science problem solving essay questions (Y)totaling 10 questions. The results showed that there was a positive relationship between scientific literacy skills andscience problem solving, which was 0.94 with a regression equation Y=18.65 + 1.09 X and a determination coefficient of0.97%, this means that scientific literacy skills have contribution of 94.04% to problem solving ability. Keywords:Ability, Science Literacy, Problem Solving, Science